If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27a + 9b + -3c + d = 2 Solving 27a + 9b + -3c + d = 2 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-9b' to each side of the equation. 27a + 9b + -3c + -9b + d = 2 + -9b Reorder the terms: 27a + 9b + -9b + -3c + d = 2 + -9b Combine like terms: 9b + -9b = 0 27a + 0 + -3c + d = 2 + -9b 27a + -3c + d = 2 + -9b Add '3c' to each side of the equation. 27a + -3c + 3c + d = 2 + -9b + 3c Combine like terms: -3c + 3c = 0 27a + 0 + d = 2 + -9b + 3c 27a + d = 2 + -9b + 3c Add '-1d' to each side of the equation. 27a + d + -1d = 2 + -9b + 3c + -1d Combine like terms: d + -1d = 0 27a + 0 = 2 + -9b + 3c + -1d 27a = 2 + -9b + 3c + -1d Divide each side by '27'. a = 0.07407407407 + -0.3333333333b + 0.1111111111c + -0.03703703704d Simplifying a = 0.07407407407 + -0.3333333333b + 0.1111111111c + -0.03703703704d
| 8x-26=6x+2 | | lnx+ln(x-1)=ln(x+6) | | -91/-7= | | -18x^3+923x^2-9603x+48446-17x^3-450x^2+6392x-14764= | | -(7-6a)-(5+5a)-16=-(2-5a)+(-a)+1 | | 10x^2-19xy-15y^2=0 | | 5x+26=7x-20 | | 3x^2=-213 | | X-7=5+3x | | m^(2/3) | | -5(4n+3)=30 | | -4(9+2x)=-20 | | m^2/3 | | z+81=9+7 | | x-((1/3)x)-((1/2x))-5=0 | | (2a^2b-1/2ab^3)^3 | | 81=9z-7 | | z+81=9-7 | | -96+7x=-3x+54 | | 5y/3-4/3=7 | | 3[5-(4-4x)]+2x=2(7x+2)-1 | | (3x-12)/4=(6x-39)/3 | | 1800-7w= | | 5(4z+6)-2(x-4)=7z(z+4)-z(7z-2)-48 | | cos(0.5x)-3x=0 | | -16t^2+60t+6=45 | | 3x-12/4=6x-39 | | 11(v+3)-3v=2(4v+4)-15 | | 2x-6x+7x-8x= | | -16t^2+60t+6=42 | | 3(x-4)/4=6(x-5)/3 | | 3(x-4)/4=6(x-5) |